Conjugate heat transfer in nonuniform thick-walled cavities filled with NEPCM-water nanofluids - Vemula, Rajesh; Öztop, Hakan Fehmi (Emerald Group Publishing Ltd, 2026)
PurposeThe purpose of this study is to focus on a numerical assessment of natural convection and melting behavior in a square enclosure containing a water-based nano-encapsulated phase change material (NEPCM) nanofluid, with particular attention to the influence of a bottom wall of non-uniform thickness and differentially heated vertical boundaries.Design/methodology/approachA two-dimensional square enclosure featuring a bottom wall of non-uniform thickness and vertical boundaries maintained at different temperatures is analyzed. The governing equations are formulated within a Galerkin finite element framework and solved numerically, with the accuracy of the model verified against well-known benchmark cases. A systematic parametric study is performed for the Stefan number (0.2 <= Ste <= 0.7), fusion temperature (0.1 <= theta f <= 0.9), particle loading (0 <= phi <= 0.05), wall-to-fluid conductivity ratio (0.1 <= Rk <= 10) and Rayleigh number (103 <= Ra <= 106).FindingsThe presence of NEPCM particles leads to a noticeable improvement in heat transfer compared with the base fluid, owing to the combined effects of sensible heat transport and latent heat storage during the phase change process. The maximum Nuavg occurs at Ste = 0.2, giving approximately 12.5% enhancement, which decreases to approximately 10.9% as Ste increases. Fusion temperature induces a non-monotonic variation, with Nuavg peaking near approximately theta f=0.2 and declining toward theta f= 0.9. Increasing phi to 0.05 improves Nuavg by approximately 10%-15%. At low Rk = 0.1, absolute Nuavg is highest, but relative enhancement rises to approximately 15.1% at Rk = 10. With Ra increasing from 103 to 106, Nuavg increases substantially, though relative gain reduces from approximately 15.0% to approximately 10.1%.Research limitations/implicationsThe NEPCM is represented as nanocapsules with an n-octadecane core and a PMMA shell, and the mixture with the water base fluid is treated as a dilute suspension. As a result, possible interactions between particles and agglomeration phenomena are not considered, which could influence the reliability of the results when higher particle loadings are used.Practical implicationsThe use of NEPCM-based nanofluids in thermal energy storage applications has the potential to significantly enhance heat transfer performance in a variety of engineering systems. By combining latent heat storage with improved thermal transport properties, these fluids offer an effective means for achieving better thermal regulation in advanced thermal management devices.Originality/valueThis study presents a comprehensive numerical analysis of phase change and buoyancy-driven flow in an enclosure with non-uniform wall thickness filled with an NEPCM-water nanofluid, and it delivers new quantitative understanding of the combined roles of latent heat storage and wall conduction in improving heat transfer performance.
Keywords: Natural convection; Conjugate heat transfer; NEPCM-water nanofluid; Non-uniform wall thickness; Phase change; Finite element method